ENGINEERING EDUCATION FOR INNOVATION ECONOMIC DEVELOPMENT OF CHUVASH REPUBLIC - Vladimir A. Shchedrin (Высшее образование в России)
The article analyzes the state of engineering education in Chuvash Republic after signing the Bologna Declaration and the introduction of the new FSES VPO of the third generation; proposes measures for the preservation of the basic foundations of national engineering education. The main idea concerns the formation of a modified baccalaureate model including various modulars and profiles with the different education periods. This model should combine the methodological principles of Bologna Declaration and the advantages of Russian engineering education.